2018
DOI: 10.1021/acsami.8b20245
|View full text |Cite
|
Sign up to set email alerts
|

Controllably Enhancing Stretchability of Highly Sensitive Fiber-Based Strain Sensors for Intelligent Monitoring

Abstract: Functional strain sensing is essential to develop health monitoring and Internet of Things. The performance of either narrow sensing range or low sensitivity restricts strain sensors in a wider range of future applications. Attaining both high sensitivity and wide sensing range of a strain sensor remains challenging. Herein, a cluster-type microstructures strategy is proposed for engineering high stretchability of highly sensitive strain sensor. The resistance change of the strain sensor is determined by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 42 publications
1
38
0
2
Order By: Relevance
“…The slower strain rate of 0.1 Hz did not show this phenomenon. Piezoresistive sensors have been reported that are able to track at higher strain rates, although they do not utilize polymer composites and rely on crack formation and decreased contact as the mechanism of piezoresistivity, avoiding this effect from the polymer mechanical properties [78]. If fast strain rates are required, the use of capacitive sensors are more appropriate, since they do not depend on the piezoresistive mechanism susceptible to rate-dependent hysteresis, and can sense accurately at strain rates upwards of 50% s −1 [79].…”
Section: Discussionmentioning
confidence: 99%
“…The slower strain rate of 0.1 Hz did not show this phenomenon. Piezoresistive sensors have been reported that are able to track at higher strain rates, although they do not utilize polymer composites and rely on crack formation and decreased contact as the mechanism of piezoresistivity, avoiding this effect from the polymer mechanical properties [78]. If fast strain rates are required, the use of capacitive sensors are more appropriate, since they do not depend on the piezoresistive mechanism susceptible to rate-dependent hysteresis, and can sense accurately at strain rates upwards of 50% s −1 [79].…”
Section: Discussionmentioning
confidence: 99%
“…Extracting the characteristic value by fitting the linear function or matrix and using calculus is relatively complicated and difficult. [9,11,15] In this work, the characteristic range value of the resistance, the calculation function of the peak value and the time comparison of the peak and valley point were used for evaluation.…”
Section: Resistance Characteristic Value and Recognition Of Human Gaimentioning
confidence: 99%
“…Every material has its own conductivity; however, their working strain range is small and thus limits their practical application [8,13,14]. In the design of a strain sensor corresponding to human movement, the following key factors must be considered-large strain range, fast recovery deformation and high sensitivity [15][16][17]. Some special sensors (such as electromyographic signal) can be used to sense the activity of muscle and have great potential for human movement detection [5,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, by combining traditional textile technology with electrical engineering, e-textile has become an attractive candidate for wearable sensors ( Afroj et al., 2019 ; Hu et al., 2019 ; La et al., 2018 ; Wang et al., 2021 ; Zhao et al., 2019b ). Specifically, fiber strain sensors, known as the convergence of strain sensing materials (conductive materials) and textile platforms, have been used to monitor various human activities ( Gupta et al., 2018 ; Li et al., 2017 ; Liao et al., 2019 ; Yao et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%